Construct Validity and Internal Consistency of the Italian Version of the PedsQLTM 4.0 Generic Core Scale and PedsQLTM 3.0 Cerebral Palsy Module - Ilaria Pedrinelli; Sofia Biagi; Domenico Marco Romeo; Elisa Musto; Valeria Fagiani; Martina Lanza; Erika Guastafierro; Alice Colombo; Andrea Giordano; Cristina Montomoli; Cristiana Rezzani; Tiziana Casalino; et al. (Children)
Background: Health-related quality of life (HRQoL) has emerged as a meaningful outcome measure in clinical trials and healthcare interventions in children with cerebral palsy (CwCP). We assessed the construct validity and internal consistency of the Italian version of the Paediatric QoL inventory (PedsQLTM) 4.0 Generic Core Scales (GCS) and PedsQLTM 3.0 Cerebral Palsy Module (CPM). Methods: A total of 125 CwCP and their parents were enrolled. Participants completed both the GCS and the CPM modules, and the results were compared to those of a sample of 121 healthy peers and their parents. The dimensionality of the two modules was assessed through exploratory factor analysis. Construct validity was assessed by a known-groups method evaluating the differences between CwCP and healthy sample. Results: Only a few GCS subscales were unidimensional, while all CPM subscales proved to be unidimensional, except for the Speech and Communication subscales of child self-reports. GCS internal consistency was good for all subscales of the parent proxy-reports, as well as for the Physical Activities and Psychosocial Health subscales of child self-reports. CPM internal consistency was good for both parent proxy-reports and—with a few exceptions—child self-reports. As for the PedsQLTM validity, the GCS proved effective in discriminating between CwCP and healthy participants; the CPM showed a significant association between lower neurofunctional abilities and lower HRQoL. Parent–child concordance shows that child self-report scores were always higher than the those of the proxy-reports for both the GCS and CPM modules. Conclusions: The present study confirms the internal consistency and construct validity of the Italian version of both PedsQLTM modules. In CwCP, greater functional disability resulted in lower HRQoL scores, and there was significant discrepancy between the parent and child ratings.